Balinese Usada as a biocultural knowledge system revealed through the chemodiversity of two Ocimum species - I NYOMAN ARSANA; PUTU LAKUSTINI CAHYANINGRUM; ANAK AGUNG AYU SAUCA SUNIA WIDYANTARI (Society for Indonesian Biodiversity, 2026)
Abstract. Arsana IN, Cahyaningrum PL, Widyantari AAASS. 2026. Balinese Usada as a biocultural knowledge system revealed through the chemodiversity of two Ocimum species. Biodiversitas 27 (3): d270337. https://doi.org/10.13057/biodiv/d270337. Ocimum tenuiflorum and Ocimum gratissimum are widely used in the Balinese Usada, a biocultural knowledge system that integrates plant diversity and culturally transmitted medical practices. However, systematic documentation linking comparative phytochemical diversity with functional differentiation between Ocimum species within this context remains limited. This study aims to compare the phytochemical profiles, antioxidant activity, and antibacterial activity of O. tenuiflorum and O. gratissimum to elucidate species-level differentiation as a character of biocultural biodiversity. The research procedure began with the process of extracting separately the leaves of O. tenuiflorum and O. gratissimum using ethanol, methanol, and hexane solvents. The active compounds were analyzed with Gas Chromatography-Mass Spectrometry (GC-MS). Total phenols and tannins were analyzed using the Folin-Ciocalteu reagent. Total flavonoids using quercetin. Antioxidant activity was analyzed using 2,2-Diphenyl-1-Picrylhydrazyl (DPPH). The antibacterial activity was tested using the diffusion method on Mueller-Hinton agar media, with four types of bacteria: Streptococcus mutans ATCC 25175, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853. The results revealed that clear interspecific phytochemical differentiation of O. gratissimum was characterized by a predominance of phenylpropanoids, particularly eugenol, whereas O. tenuiflorum was dominated by methyleugenol and sesquiterpenes such as caryophyllene. These chemical differences were accompanied by distinct functional responses, with O. gratissimum exhibiting better antioxidant capacity (IC₅₀ 43.92±0.03 μg/mL) compared to O. tenuiflorum (IC₅₀ 79.45±0.01 μg/mL). Both species exhibited differently antibacterial inhibition patterns against the tested bacteria, indicating species-specific functional traits rather than bioactivity. Overall, this study demonstrates that interspecific chemodiversity in Ocimum reflects species-level differentiation within the Balinese Usada system. Integrating comparative phytochemical and functional analyses within a biocultural framework, the findings contribute to biodiversity science by highlighting chemical variation as a functional character of biocultural biodiversity.